The wintering waterfowl of Turkmenistan - Rustamov, Eldar A (Wildfowl, 2025)
Winter counts of waterfowl were carried out from 1972-1990 on the eastern shores of the Caspian Sea and on inland waterbodies of Turkmenistan. Local and regional population trends are described revealing a considerable decline in waterfowl numbers. This is thought to be due to a combination of the disastrous effects of human interference, a serious outbreak of botulism and a redistribution of birds wintering in the Caspian as a result of cold winters.